Shipwreck On The Pirate Islands - Stilton, Geronimo
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. My sister had come up with a new way to torment me. She'd combined my two least favorite things - travel and ghosts! Thea had heard rumors of a haunted pirate treasure buried on a desert island. And before I could say "avast ye scurvy rats," she'd dragged me into her treasure hunt!